The Body in Motion An Introduction (Body in motion., 2010)
In action or at rest, the human body is always in motion. This program uses vivid animations and real-life examples to show how the musculoskeletal and cardiorespiratory systems work and how they influence and respond to movement. Chapters include Introduction, The Skeletal System, The Muscular System, The Respiratory System, The Circulatory System, and Conclusion.